Human development in the era of globalization essays in honor of Keith B. Griffin - Griffin, Keith B.; Boyce, James K.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
Honoring Keith Griffin's more than 40 years of fundamental contributions to the discipline of economics, the papers in this volume reflect his deep commitment to advancing the well-being of the world's poor majority and his unflinching willingness to question conventional wisdom as to how this should be done.
pt. 1. Perspectives on Chinese development -- pt. 2. Agriculture and rural poverty -- pt. 3. Dimensions of human development -- pt. 4. Globalization and inequality -- pt. 5. Strategies for reducing poverty and inequality.
Includes bibliographical references and index.
Keywords: Economic policy; Poverty; Electronic books